Resident evil : retribution [videorecording (Blu-Ray)] - Anderson, Paul, 1965-; Jovovich, Milla; Guillory, Sienna, 1975-; Rodriguez, Michelle (Sony Pictures Home Entertainment, 2012)
Alice fights alongside a resistance movement in the continuing battle against the Umbrella Corporation and the undead.